1993
DOI: 10.1111/j.1600-0536.1993.tb03508.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure, skin protection and occupational skin diseases in the glass‐fibre‐reinforced plastics industry

Abstract: A total of 100 workers, 86 from the glass-fibre-reinforced plastics (GRP) industry, 11 from polystyrene production and 3 from polyester resin coating manufacture, were examined for occupational skin hazards and for evaluation of skin protection. The workers had been exposed to many chemicals. Those working in the GRP industry had also been exposed to glass fibre and to dust produced by finishing work. 94% used protective gloves. 22 workers, all employed in the GRP industry, had contracted occupational skin dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 21 publications
2
33
1
Order By: Relevance
“…Of the Japanese FRP workers in this study, 58.8% reported having a history of skin problems which is in agreement with a Finnish study 3) where 62% of the Finish workers of FRP factories reported skin problems since initial employment in FRP manufacture.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of the Japanese FRP workers in this study, 58.8% reported having a history of skin problems which is in agreement with a Finnish study 3) where 62% of the Finish workers of FRP factories reported skin problems since initial employment in FRP manufacture.…”
Section: Discussionsupporting
confidence: 80%
“…Skin problems of FRP workers may arise from a number of causative agents including resin, styrene, auxiliary agents, hardeners [2][3][4][5][6][7][8][9][10][11] , glass fiber [12][13][14] and dust comprising of shortened glass fiber and plastic particles 17) . Glass fiber with a diameter greater than 4 µm can cause irritation and dermatitis 14) and all factories surveyed were using glass fiber with greater diameters (11 or 23 µm) and so workers were at risk of developing dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…13 One study found that skin disorders in a group of workers similar to those at DCM were common but the symptoms were mild and did not cause many lost work days. 14 The findings of this HHE are consistent with this observation. The fiberglass found on the skin of workers in this study was 10 µm in diameter.…”
Section: Medicalsupporting
confidence: 81%
“…The previous studies have shown that FRPs strengthening is very effective to alter the performance of concrete members. Several studies reported skin problems such as irritant and allergic contact dermatitis for workers during synthetic FRP manufacturing and application procedure [13,14]. One possible solution to the aforementioned problems would be the replacement of synthetic fibers with natural fibers.…”
Section: Introductionmentioning
confidence: 99%